Methylenetetrahydrofolate reductase polymorphisms and elevated plasma homocysteine levels in small vessel disease - Lei Chen; Chunhua Wu; Zhaoying Dong; Shanshan Cao; Ning Ren; Xiaoyan Yan (Brain and Behavior, 2023)
Abstract Introduction Despite its public health importance, the causes of small vessel disease (SVD) are not fully understood. The presence of SVD in monogenic twins indicates the involvement of genetic factors in the pathogenesis of this disease. The purpose of this study was to investigate the association of methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms with SVD risk. Methods Patients with SVD and matched controls were recruited from Tianjin Union Medical Center and Tianjin Huanhu Hospital. Clinical and laboratory data were collected. Plasma total homocysteine (tHcy) and folate levels were measured, and MTHFR rs1801133 (C677T) and rs1801131 (A1298C) single‐nucleotide polymorphisms were genotyped. We analyzed potential associations among SVD and MTHFR polymorphisms, tHcy, and folate levels. Results Patients with SVD displayed significantly decreased plasma folate levels (Z = –3.537, p < .001) and increased tHcy levels (Z = 4.910, p < .001) compared with controls. Significantly different plasma tHcy levels were associated with rs1801133 (χ2 = 6.664, p = .036), and post hoc analysis indicated higher plasma tHcy levels in individuals carrying the TT allele compared with levels in those carrying the TC allele (Z = 2.478, p = .013). No significant differences in tHcy levels were observed for rs1801131 alleles. The genotype and allele frequencies of rs1801133 were different between SVD and control groups (χ2 = 9.378, p = .009). There was no significant difference in distributions of rs1801131 genotypes between the two groups, and multivariable logistic regression analysis showed that rs1801131 and rs1801133 were not significantly associated with the risk of SVD. Conclusions Our study indicates that an elevated plasma tHcy level is independently associated with the development of SVD. Although MTHFR rs1801133 is linked to increased plasma homocysteine (Hcy) levels, it is not a risk factor for SVD. rs1801131 is not related to Hcy levels or SVD risk.